2004
DOI: 10.1074/jbc.m310486200
|View full text |Cite
|
Sign up to set email alerts
|

MAPKAP Kinase 2 Phosphorylates Tristetraprolin on in Vivo Sites Including Ser178, a Site Required for 14-3-3 Binding

Abstract: MAPKAP kinase 2 (MK2) is required for tumor necrosis factor synthesis. Tristetraprolin (TTP) binds to the 3-untranslated region of tumor necrosis factor mRNA and regulates its fate. We identified in vitro and in vivo phosphorylation sites in TTP using nanoflow high pressure liquid chromatography microelectrospray ionization tandem mass spectrometry and novel methods for direct digestion of TTP bound to affinity matrices (GSHbeads or anti-Myc linked to magnetic beads MK21 mediates several p38␣,␤ MAP kinase-dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
299
3
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 254 publications
(314 citation statements)
references
References 53 publications
9
299
3
3
Order By: Relevance
“…COX-2, CSF2 and IL-2 genes are dysregulated in the absence of TTP (Carballo et al, 2000;Ogilvie et al, 2005;Phillips et al, 2004), and it seems likely that expression of other inflammatory mediators will also prove to be controlled by TTP. Inflammatory mRNAs can be stabilized via the phosphorylation and inactivation of TTP by MAPK-activated protein kinase 2, a kinase that is activated by p38 MAPK (Carballo et al, 2001;Chrestensen et al, 2004;Stoecklin et al, 2004). At least in cells of the myeloid lineage, this appears to be the principal mechanism for post-transcriptional regulation of inflammatory genes by the p38 MAPK pathway.…”
Section: Tristetraprolinmentioning
confidence: 99%
“…COX-2, CSF2 and IL-2 genes are dysregulated in the absence of TTP (Carballo et al, 2000;Ogilvie et al, 2005;Phillips et al, 2004), and it seems likely that expression of other inflammatory mediators will also prove to be controlled by TTP. Inflammatory mRNAs can be stabilized via the phosphorylation and inactivation of TTP by MAPK-activated protein kinase 2, a kinase that is activated by p38 MAPK (Carballo et al, 2001;Chrestensen et al, 2004;Stoecklin et al, 2004). At least in cells of the myeloid lineage, this appears to be the principal mechanism for post-transcriptional regulation of inflammatory genes by the p38 MAPK pathway.…”
Section: Tristetraprolinmentioning
confidence: 99%
“…Phosphorylation of TTP in the transfected HEK293 cells was further supported by in vivo labeling of proteins with radioactive phosphate, followed by Ni-NTA purification, or by immunoprecipitation with the anti-MBPhTTP serum ( Figure 8A). However, the T271A mutation but not the S186A mutation in hTTP, corresponding to two of the MK2-phosphorylated sites at S264 and S178 of mTTP (23), modestly altered the gel mobility of the mutant protein ( Figure 8A). …”
Section: Phosphorylation Of Ttp In Vivo and In Vitromentioning
confidence: 99%
“…The active form of the MBP-hTTP fusion protein binding to TNF mRNA ARE appears to be in the form of an oligomer rather than a monomer (9). TTP purified from E. coli can be phosphorylated by multiple mitogen-activated protein (MAP) kinases in vitro (9,(20)(21)(22)(23)(24) with kinetics similar to those of other protein substrates (9). Finally, the tandem zinc finger peptide of TTP binds ARE sequences with high affinity (10).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that stimulation with LPS results in a strong and rapid induction of TTP mRNA in mouse macrophages (Mahtani et al, 2001). However, LPS stimulation does not enhance the TTP-mediated degradation of ARE-containing mRNA because it also activates p38 MAPK, which can phosphorylate and inactivate TTP (Chrestensen et al, 2004;Stoecklin et al, 2004). Stimulation with IFN-γ (Sauer et al, 2006), IL-10 (Schaljo et al, 2009) or nicotine (Joe et al, 2011) has been reported to induce TTP expression but not p38 MAPK activity and thus these agents increase the induction of mRNA decay by TTP.…”
Section: Discussionmentioning
confidence: 99%